A review on ultraviolet light treatment for emissions of livestock gases, odor control in waste management, and disinfection of common environmental pathogens - T.A.N.T. Perera; H.A.T.N. Perera; D.M.N.A. Dissanayake; M.A.S.K Dias; P.P. Ruwanpathirana; G.Y. Jayasinghe (Waste Management Bulletin)
The livestock sector’s emission of greenhouse gases and hazardous gases, has contributed significantly to environmental pollution, including climate change and global warming. Furthermore, the accumulation of microbial pathogens in livestock waste, including Salmonella and Escherichia coli, poses a risk to food safety and health. Several strategic solutions have been developed to control these impacts, ensuring compliance with environmental regulations and industry sustainability. UV irradiation has emerged as an effective technology in controlling emissions from the livestock sector, based on photolysis and photo-catalysis. A laboratory experiments prove that using UV in combination with filtration, the removal rate of CO2, NH3, N2O, VOC, pathogenic bacteria, and dust is 3.8 – 4.4%, 2.6–18.07%, 6.9 – 12.2%, 80 – 100%, 99.4%, and 95% respectively. Although photo-catalysis is highly effective in the elimination of gaseous compounds and pathogen, dust control is mainly done by filtration processes. This paper provides a comprehensive review of existing literature on global livestock emissions and pathogenic microorganisms, existing mitigation practices, UV treatment for livestock emissions mitigation, and the opportunities, challenges, and future perspectives and disinfection of common environmental pathogens of livestock emissions.